Cycle Time Optimization of Chamomile Package 120 MI Product at Blow Molding Process - Yuni Hermawan; I Made Astika (Jurnal Energi Dan Manufaktur, 2009)
Chamomile is a package which is applied for cosmetic. In industry this package is being processed by blow molding. Thereare many parameters that influence cycle time during production; in this project only three of them were varied, i.e. blowingpressure, blowing time and stopping time. Each parameter is determined three chosen level. Middle level is taken fromstandard setting of machining which is being used by industry. Top and bottom level is randomized. Three stopping time are0.1, 0.55, and 1.0 second. Blowing time are 10.5, 11.5 and 12.5 second. Where as, blowing pressures is 4, 5 and 6 bar.Combination of among levels is based on Box Behnken design. Those three parameters are called variable process. In theother hand, variable responses are cycle time and net weight. Each combination is replicated 5 times and then averaged. Thedata then is processed by using Minitab version 14th. Square regression of the model for cycle time is ?CT = 21,1300 - 0,0912X1 + 0,2000 X2 + 0,6313 X3 + 0,6100 X12 + 0,6975 X22 – 0,1000 X1 X2 – 0,1725 X1 X3 + 0,1100 X2 X3 and Net = 19,2933 –0,0088 X1 + 0,0175 X2 + 0,0712 X3 + 0,0133 X 21 + 0.0158 X22- 0.0217 X 23 + 0.0125 X1X2 - 0,0150 X1 X3 for product netweight. Where X1 is blowing pressure, X2 is blowing time and X3 is stopping time.The model developed then tested by lack offit testing, variance by ANOVA and R square. Second stage of model testing is residual test. Three tests are carry out, i.e.identically test and independency test and normality. Optimization of both values, cycle time and net weight, are searched byResponse Surface Method. By the method it is found that the optimum condition of cycle time is 20.5 seconds and net weightis 19.19 grams. The optimum condition is achieved when stopping is 0.1 second, blowing time 11.35 second and blowingpressure 5.1 bars.